The Late Triassic World Earth in a Time of Transition (Topics in Geobiology, 2018)
This volume presents the latest science on all significant geological and paleontological aspects of the Earth during the Late Triassic Period. Rather than presenting a collection of narrowly focused research papers, the volume consists of a series of peer-reviewed chapters on specific aspects of the Late Triassic world (e.g., tectonics, magmatism, paleobotany, climate, etc.), all authored by experts in the subject of their respective chapters. Each chapter reviews and summarizes the latest findings in these fields and also includes a review of the pertinent literature. The author list is very broadly international and forms a veritable who's who of expertise in these fields. The book is loosely organized to present the physical aspects of Earth during the Late Triassic at the outset, followed by the paleontological aspects. The latter section is further organized to present the record of the marine environment first before moving onto land, with fauna followed by flora. The volume closes with a review of the end-Triassic extinctions.